The scavenging capacity of DMBT1 is impaired by germline deletions - Bikker, Floris J.; End, Caroline; Ligtenberg, Antoon J. M.; Blaich, Stephanie; Lyer, Stefan; Renner, Marcus; Wittig, Rainer; Nazmi, Kamran; Amerongen, Arie Van Nieuw; Poustka, Annemarie; Veerman, Enno C. I.; Mollenhauer, Jan (Immunogenetics, 2017)
The Scavenger Receptor Cysteine-Rich (SRCR) proteins are an archaic group of proteins characterized by the presence of multiple SRCR domains. They are membrane-bound or secreted proteins, which are generally related to host defense systems in animals. Deleted in Malignant Brain Tumors 1 (DMBT1) is a SRCR protein which is secreted in mucosal fluids and involved in host defense by pathogen binding by its SRCR domains. Genetic polymorphism within DMBT1 leads to DMBT1-alleles giving rise to polypeptides with interindividually different numbers of SRCR domains, ranging from 8 SRCR domains (encoded by 6 kb DMBT1 variant) to 13 SRCR domains (encoded by the 8 kb DMBT1 variant). In the present study, we have investigated whether reduction from 13 to 8 amino-terminal SRCR domains leads to reduction of bacterial binding. The 6 kb variant bound 20–45% less bacteria compared to the 8 kb variant. These results support the hypothesis that genetic variation in DMBT1 may influence microbial defense.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Genetic polymorphism; Microbial defense; Pathogen binding; SRCR domain